2017
DOI: 10.1017/s0007114517001428
|View full text |Cite
|
Sign up to set email alerts
|

Dietaryl-tryptophan leaves a lasting impression on the brain and the stress response

Abstract: Comparative models suggest that effects of dietary tryptophan (Trp) on brain serotonin (5-hydroxytryptamine; 5-HT) neurochemistry and stress responsiveness are present throughout the vertebrate lineage. Moreover, hypothalamic 5-HT seems to play a central role in control of the neuroendocrine stress axis in all vertebrates. Still, recent fish studies suggest long-term effects of dietary Trp on stress responsiveness, which are independent of hypothalamic 5-HT. Here, we investigated if dietary Trp treatment may r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
2
16
0
1
Order By: Relevance
“…Instead they coincided with changes in dopaminergic neurochemistry in this brain part, effects which may be related to elevated activity of the kynruneric pathway, as discussed in section The Kynurenic pathway. Similar results were shown in the study performed by Höglund et al (7), where 5-HTergic activity in hypothalamus did not follow the long term Trp induced suppressive effect on post stress cortisol levels. The latter study also included telencephalon and 5-HT activity followed the same general pattern as cortisol in this brain part.…”
Section: Trp and The Neuroendocrine Stress Responsesupporting
confidence: 91%
See 1 more Smart Citation
“…Instead they coincided with changes in dopaminergic neurochemistry in this brain part, effects which may be related to elevated activity of the kynruneric pathway, as discussed in section The Kynurenic pathway. Similar results were shown in the study performed by Höglund et al (7), where 5-HTergic activity in hypothalamus did not follow the long term Trp induced suppressive effect on post stress cortisol levels. The latter study also included telencephalon and 5-HT activity followed the same general pattern as cortisol in this brain part.…”
Section: Trp and The Neuroendocrine Stress Responsesupporting
confidence: 91%
“…However, in recent studies in sea water reared Atlantic salmon ( Salmo salar ), the suppressive effect on post-stress plasma cortisol seems to appear between 2 and 8 days after terminating the Trp supplementation. Moreover, in Atlantic salmon, this suppressive effect was still present at 21 days post Trp supplementation (7, 53). Basic et al (53) suggested that such slow acting Trp-induced alterations of HPI-axis reactivity could be related to smoltification, a process where salmonid fish adapt to sea water.…”
Section: Trp and The Neuroendocrine Stress Responsementioning
confidence: 97%
“…role in mood and sleep disorders as well as depression due to its interaction with serotonergic and GABAergic neurotransmission (Mendelson and Basile, 2001). Similarly, tryptophan is not only an essential amino acid for protein synthesis but also a precursor of several biological mediators involved in stress response, antioxidant system, behavioral response, and immune system (Firk and Markus, 2009;Hoglund et al, 2017). Decreased tryptophan levels have been linked to lower serotonin levels, likely setting the basis for the establishment of neuropsychological symptoms including depression, anxiety, irritability, attention deficits, and insomnia (Jenkins et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in S. salar , post‐stress cortisol levels decreased 8 and 21 days after a 7‐day period tryptophan administration (Höglund et al . ). The importance of tryptophan administration time on serotonergic activity and cortisol response has been also reported earlier in O. mykiss (Lepage et al .…”
Section: Effects Of Tryptophan On 5ht Synthesis Behaviour and Stressmentioning
confidence: 97%